Atherosclerotic lesions of brachiocephalic arteries and issues of surgical correction of symptomatic and asymptomatic carotid stenosis - N. I. Glushkov; M. A. Ivanov; A. S. Artemova; A. Yu. Apresyan; A. D. Gorovaya; А. A. Uryupina (Вестник хирургии имени И.И. Грекова)
The objective of the study was to evaluate the results of carotid endarterectomy in patients with symptomatic and asymptomatic course of hemodynamically significant stenosis of carotid arteries.Material and methods. The work was based on observations of 88 patients: the main group included 28 patients with asymptomatic lesion, the control group – 60 patients with symptomatic critical carotid stenosis.Results. There was a predominance of contralateral carotid stenosis, changes in vertebral arteries in the control group. Features of atherosclerotic lesion of carotid arteries associated with the severity of metabolic disorders, perioperative fluctuations of hemodynamics, time of clamping of carotid arteries.Conclusion. Aggressive course of symptomatic carotid stenosis requires correction of metabolic disorders in the perioperative and in the distant periods, as well as monitoring of hemodynamic abnormalities.